Path analysis model of the development of handicraft industries in Kelantan, Malaysia - Redzuan, Ma'rof; Aref, Fariborz (Marsland Press, 2010)
This study identify factors that contribute to the development of handicraft industries. The focus is on batik industries. The study was carried out in the District of Kota Bharu in the State of Kelantan, Malaysia, and targeted the entrepreneurs in the batik handicraft enterprises. The study is based upon both quantitative and qualitative analysis of material derived from field-work in several villages in the study area. The analysis of data employed path-analysis model in order to determine the factors that contribute to the explanation of the dependent variable – the development of the industries. The finding show that the selected factors have contributed significantly in the explanation of the development of the industries. The findings imply that it is imperative to consider and understand the local resources, skills, attitudes and aspirations in any government efforts to foster the development of these handicraft industries.